The Apprenticeship-to-Work Transition : Experimental Evidence from Ghana - Hardy, Morgan; Mbiti, Isaac; McCasland, Jamie; Salcher, Isabelle (World Bank, Washington, DC, 2019)
This paper examines the effects of a government-sponsored apprenticeship training program designed to address high levels of youth unemployment in Ghana. The study exploits randomized access to the program to examine the short-run effects of apprenticeship training on labor market outcomes. The results show that apprenticeships shift youth out of wage work and into self-employment. However, the loss of wage income is not offset by increases in self-employment profits in the short run. In addition, the study uses the randomized match between apprentices and training providers to examine the causal effect of characteristics of trainers on outcomes for apprentices. Participants who trained with the most experienced trainers or the most profitable ones had higher earnings. These increases more than offset the program's negative treatment effect on earnings. This suggests that training programs can be made more effective through better recruitment of trainers.